1993
DOI: 10.1209/0295-5075/24/4/007
|View full text |Cite
|
Sign up to set email alerts
|

Extended Self-Similarity in the Dissipation Range of Fully Developed Turbulence

Abstract: In this letter we report further experimental evidence of extended self-similarity in the structure functions of the velocity field of fully developed turbulence. We study the behaviour of high-order structure functions close to the Kolmogorov scale η where extended self-similarity is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 6 publications
9
103
0
Order By: Relevance
“…1) with a constant energy flux for k ∈ [5, 20] and maximally helical vortex tubes are found, as predicted in [10] and shown in [11,12]. Finally, the anomalous exponents of longitudinal structure functions are in excellent agreement with previous studies [1] up to order p = 8 (see Table I), including analysis without using the extended self-similarity (ESS) hypothesis [13].…”
supporting
confidence: 88%
“…1) with a constant energy flux for k ∈ [5, 20] and maximally helical vortex tubes are found, as predicted in [10] and shown in [11,12]. Finally, the anomalous exponents of longitudinal structure functions are in excellent agreement with previous studies [1] up to order p = 8 (see Table I), including analysis without using the extended self-similarity (ESS) hypothesis [13].…”
supporting
confidence: 88%
“…In this sense, ESS enables one to extend the scaling range to the complete range of separation scales examined, as shown empirically by [28][29][30] and references therein, and provides another way to characterize the dependence of the scaling exponent ξ (q) on q. Extended self-similarity is described by the following power-law relationship between sample structure functions of different orders [31,32] …”
Section: Scaling Of Statisticsmentioning
confidence: 93%
“…Though nonlinear variation of ξ(q) with q is also reproduced by the fractional Laplace model of Meerschaert et al (2004) (see Kozubowski et al, 2006;Ganti et al, 2009), the latter does not include cutoffs and thus fails to reproduce observed breakdown in power-law scaling at small and large lags. Benzi et al (1993aBenzi et al ( ,b, 1996 discovered empirically that the range s I < s < s II of separation scales over which velocities in fully developed turbulence (where Kolmogorov's dissipation scale is assumed to control s I ) scale according to Eq. (2) can be enlarged significantly, at both small and large lags, through a procedure they called Extended SelfSimilarity (ESS).…”
Section: Introductionmentioning
confidence: 99%